2021
DOI: 10.3390/metabo11050327
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling from an Asymptomatic Ferret Model of SARS-CoV-2 Infection

Abstract: Coronavirus disease (COVID-19) is a contagious respiratory disease that is causing significant global morbidity and mortality. Understanding the impact of the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) infection on the host metabolism is still in its infancy but of great importance. Herein, we investigated the metabolic response during viral shedding and post-shedding in an asymptomatic SARS-CoV-2 ferret model (n = 6) challenged with two SARS-CoV-2 isolates. Virological and metabolic analyses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 57 publications
(76 reference statements)
4
28
0
Order By: Relevance
“…Moreover, our analysis enables the direct microbial genome comparison between permissive and protective nrMAGs. Consistent with previous reports of a relationship of the pentose phosphate pathway and SARS-CoV-2 infection 50-52 , our findings support that overrepresentation of permissive nrMAGs and underrepresentation of protective nrMAGs may upregulate the pentose phosphate pathway as their genome are shown to be highly intact in those relevant modules. In contrast, the pentose phosphate pathway related KEGG modules showed significant lower module completeness in genomes of protective nrMAGs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, our analysis enables the direct microbial genome comparison between permissive and protective nrMAGs. Consistent with previous reports of a relationship of the pentose phosphate pathway and SARS-CoV-2 infection 50-52 , our findings support that overrepresentation of permissive nrMAGs and underrepresentation of protective nrMAGs may upregulate the pentose phosphate pathway as their genome are shown to be highly intact in those relevant modules. In contrast, the pentose phosphate pathway related KEGG modules showed significant lower module completeness in genomes of protective nrMAGs.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, a previous study reported a significant increase in the levels of some intermediates of the glycolytic and pentose phosphate pathways in sera of COVID-19 positive patients 50 . Moreover, SARS-CoV-2 infection was found to be associated with changes in the regulation of the pentose phosphate pathway in both in vivo (Caco-2 cells) 51 and in vitro (ferret model) 52 studies. These findings provide evidence of potential metabolic pathways linking the gut microbes to the clinical manifestations of COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…The metabolic shift towards ATP production in the glycolytic pathway clearly, also influences other metabolic pathways, such as the pentose phosphate pathway (PPP). In these conditions, the non-oxidative phase of PPP is increased, in which glycolysis intermediates are converted into the ribose-5-phosphate required for the synthesis of the nucleic acids, which is necessary for the virus replication [25,26]. In addition, high levels of oxidized glutathione and a significant decrease in enzymes forming part of the cellular defense line against oxidative stress were found, including superoxide dismutase 1 (SOD1), glucose-6-phosphate dehydrogenase, and peroxiredoxin [27][28][29].…”
Section: Covid-19 and Rbcs Metabolismmentioning
confidence: 99%
“…The non-oxidative PPP branch converts glycolytic intermediates into ribose-5-phosphate, required for the synthesis of nucleic acids, as well as sugar phosphate precursors that are necessary for the synthesis of amino acids [ 14 ]. Moreover, SARS-CoV-2 infection was associated with changes in the PPP in a ferret model [ 15 ]. Hence, in this study, we investigated whether the anti-SARS-CoV-2 activity of 2DG can be increased by additionally targeting the non-oxidative PPP.…”
Section: Introductionmentioning
confidence: 99%